Altered fibrin network structure and fibrinolysis in intensive care unit patients with COVID‐19, not entirely explaining the increased risk of thrombosis. (1st April 2022) - de Vries, Judith J.; Visser, Chantal; Geers, Lotte; Slotman, Johan A.; van Kleef, Nadine D.; Maas, Coen; Bax, Hannelore I.; Miedema, Jelle R.; van Gorp, Eric C. M.; Goeijenbier, Marco; van den Akker, Johannes P. C.; Endeman, Henrik; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 infection is associated with an increased incidence of thrombosis. Objectives: By studying the fibrin network structure of coronavirus disease 2019 (COVID‐19) patients, we aimed to unravel pathophysiological mechanisms that contribute to this increased risk of thrombosis. This may contribute to optimal prevention and treatment of COVID‐19 related thrombosis. Patients/Methods: In this case‐control study, we collected plasma samples from intensive care unit (ICU) patients with COVID‐19, with and without confirmed thrombosis, between April and December 2020. Additionally, we collected plasma from COVID‐19 patients admitted to general wards without thrombosis, from ICU patients with pneumococcal infection, and from healthy controls. Fibrin fiber diameters and fibrin network density were quantified in plasma clots imaged with stimulated emission depletion microscopy and confocal microscopy. Finally, we determined the sensitivity to fibrinolysis. Results: COVID‐19 ICU patients ( n  = 37) and ICU patients with pneumococcal disease ( n  = 7) showed significantly higher fibrin densities and longer plasma clot lysis times than healthy controls ( n  = 7). No differences were observed between COVID‐19 ICU patients with and without thrombosis, or ICU patients with pneumococcal infection. At a second time point, after diagnosis of thrombosis or at a similar time point in patients without thrombosis, we observed thicker fibers and longer lysis times in COVID‐19 ICU patients with thrombosis ( n  = 19) than in COVID‐19 ICU patients without thrombosis ( n  = 18). Conclusions: Our results suggest that severe COVID‐19 is associated with a changed fibrin network structure and decreased susceptibility to fibrinolysis. Because these changes were not exclusive to COVID‐19 patients, they may not explain the increased thrombosis risk.